Iron deficiency anemia among Indonesian children - A. G. Soemantri; I. Sudigibia; Widjaya Widjaya (Indonesian Pediatric Society, 1984)
Iron deficiency with or without anemia as the most common deficiency anemia and its problems in Indonesia has been presented. The prevalence has been discussed and mention made about the etiology and several important factors contributing to iron deficiency; its deleterious effects on learning process, pregnancy, infection and others. The intervention program for iron deficiency anemia conducted in short and long term by the Government of Republic of Indonesia has been presented. It should be emphazised that international cooperation among research workers and supporting agencies should be encouraged to overcome the problems of nutritional anemia in Indonesia.